Language and mind - Pradhan, R. C.; University of Hyderabad. Department of Philosophy (New Delhi : Decent Books, 2006)
Contributed articles presented at the National Seminar on Language and Mind held at Hyderabad in 2004.
v. 1. A western perspective -- v. 2. The classical Indian perspective
Vol. 2 edited by: K. S. Prasad.
Papers presented at the national seminar on Language and mind Organized by the Dept. of Philosophy, University of Hyderabad.
Includes bibliographical references and index.
Keywords: LANGUAGE AND LANGUAGES -- PHILOSOPHY; PHILOSOPHY OF MIND